"IMPROVING THE METHODOLOGY OF CHILDREN'S DIALOGIC SPEECH DEVELOPMENT BASED ON A VARIATIONAL APPROACH" (IN THE CASE OF 5-6 YEAR OLD CHILDREN) (Conferencea, 2023)
In this article, we can consider "Improving the methodology of children's dialogical speech development based on a variational approach" on the example of 5-6-year-old children.